Quantitative evaluation of transmission properties of breast tissue equivalent materials under Compton scatter imaging setup. (April 2020) - Yang, Kai; Geng, Changran; Li, Xinhua; Liu, Bob
Highlights: Transmission of scattered x-ray through breast tissue phantoms was evaluated. X-ray spectrum model and breast phantom composition were experimentally validated. Three approaches: experiment, analytical calculation, and Monte Carlo simulation. The transmission curves from all three methods matched reasonably well. The quantitative results paved the base for future work on Compton scatter imaging. Abstract: To explore the potential of utilizing Compton scattered x-ray photons for imaging applications, it is critical to accurately evaluate scattered x-ray transmission properties of targeted tissue materials. In this study, scattered x-ray transmission of breast tissue equivalent phantoms was evaluated. Firstly, two validations were carried out using a primary x-ray beam at 80 kVp with both experimental measurement (ion chamber with narrow-beam setup) and analytical calculation (Spektr toolkit). The tungsten-anode x-ray spectrum model was thus validated by measuring and calculating the transmission through increasing thickness of 1100 Aluminum filters. Similarly, the composition models of breast tissue equivalent phantoms (CIRS, 012A) were validated by measuring and calculating x-ray transmission for three different breast compositions (BR30/70, BR50/50, and BR70/30). Following validation, transmission properties of Compton scattered x-ray photons were measured with a GOS based linear array detector at the 90° angle from the primary beam. The same study was performed through three independent approaches: experimental measurement, analytical calculation, and Monte Carlo simulation (GEANT4). For all three methods, the scattered x-ray photon transmission as functions of phantom thickness were determined and fit into exponential functions. The transmission curves from all three methods matched reasonably well, with a maximum difference of 6.3% for the estimated effective attenuation coefficients of the BR50/50 phantom. The relative difference among the three methods of estimated attenuation is under 3.5%. As an initial step to develop a novel Compton scatter-based breast imaging system, the quantitative results from this study paved a fundamental base for future work.